Mexico : Review Under the Flexible Credit Line Arrangement: Staff Report; and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2011)
Mexico's policy stance has focused on balancing domestic and external conditions, supporting the recovery while rebuilding policy buffers through fiscal consolidation and reserve buildup. Growth has remained resilient during the first half of 2011 and is expected to continue into 2012, albeit at a more moderate pace. Downside risks remain elevated, associated with possibly protracted low growth in the United States and bouts of heightened global risk aversion from unsettled market conditions in Europe. The Mexican peso has depreciated by about 8 percent in nominal effective terms since the beginning of the turmoil in Europe.